Direct oral anticoagulants for the treatment of venous thromboembolism in cancer patients: Potential for drug–drug interactions. (December 2018) - Riess, Hanno; Prandoni, Paolo; Harder, Sebastian; Kreher, Stephan; Bauersachs, Rupert
Highlights: Patients with cancer are at high risk of developing venous thromboembolism. Direct oral anticoagulants may overcome low molecular weight heparins limitations. Few cancer therapies interact with direct oral anticoagulants. Abstract: Patients with cancer are at high risk of developing venous thromboembolism (VTE). Although the recommended low molecular weight heparins (LMWHs) are more effective than vitamin K antagonists in treating VTE in patients with cancer, they have limitations and contraindications. Direct oral anticoagulants (DOACs) circumvent some of these limitations. Here, DOAC use for VTE treatment in patients receiving anticancer therapy is reviewed, focusing on metabolic and elimination pathways, potential drug–drug interactions and practical considerations. DOACs are typically substrates of the cytochrome P450-based metabolic pathways and/or ATP-binding cassette transporters. Although many cancer therapies influence these pathways, only a minority of these drugs interact with DOACs. Phase III DOAC trials provided encouraging safety and efficacy data for their use in cancer-associated thrombosis. Furthermore, numerous ongoing DOAC trials strive to gain a better understanding of the treatment of cancer-associated thrombosis and continue to support a role for DOACs in this setting.